STUDY BIRDS ARE TRADE IN SPLENDID BIRD MARKET, MALANG - Prakosa, Bayu Hendra; Kurniawan, Nia (Biotropika: Journal of Tropical Biology, 2015)
Splendid Bird Market was established in 1955 and located central city of Malang. The purpose of this study was to determine number of species birds are trade in Splendid Bird Market and knowing conservation status of bird traded in Splendid Bird Market, this studi started in January 1st until March 31th 2014 located at Splendid Bird Market. Tools and materials that used for collecting data are field guide bird identification of greater Sunda region and Wallacea region, camera, pocket book, handphone, and stationery. The method of collecting data consist of field observation, interview, collecting primary and secondary data. Data were analyzed using qualitative descriptive analysis. The results were found 10 ordes, 38 family, and 148Â spesies of birds. Birds that were traded in Splendid bird market mostly come from Sumatera, Java, Bali, and Borneo and the percentage of that birds is 92%. Birds like Long-tailed Shrike (Lanius schach Linnaeus 1758), Oriental-magpie Robin (Copsychus saularis, Linnaeus 1758), White-rhumped Shama (Copsychus malabaricus, Scopoli 1786), Greater Leafbird (Chloropsis sonnerati, Jardine & Selby 1827), Orange-headed Thrush (Zoothera citrina, Latham 1790), Straw-headed Bulbul (Pycnonotus zeylanicus, Gmelin 1789), and Bali Starling (Leucopsar rothschildi Stresemann 1912) were most wanted by people. Several birds were migrant birds from East Asia, based on IUCN, 90% birds were traded in Splendid Bird Market have conservation status is least concern, and singing birds are most wanted by people. Keyword : Bird, Bird market, Bird trading.